The Effect of Current Ratio, Debt to Equity Ratio, and Return on Equity Ratio Against Company Reputation - Yustikasari, Yulia; Farida, Ida (Universitas Mercu Buana, 2024)
In today's marketing world, competition between companies is no longer about product competition but rather seeking positive perceptions from consumers. Company reputation is a form of consumer perception, evaluation or assessment of the company's attributes or capabilities based on their reactions to the use of products and services, services as well as interaction and communication with the company so as to form an image of past conditions and future prospects. This research aims to analyze company reputation using stewardship and signaling theory. The dependent variable in this research is company reputation, while the independent variables in the research are Current Ratio, Debt o Equity Ratio, and Return on Equity. This research uses a sample of Real Estate and Property Companies listed on the Indonesian Stock Exchange. Data was collected using purposive sampling and tested using descriptive statistics, classical assumption test, multiple linear regression test, coefficient of determination test and hypothesis test. From the results of statistical testing it can be concluded that the Current Ratio has no effect on Company Reputation, the Debt to Equity Ratio has an effect on Company Reputation, Return on Equity has an effect on Company Reputation.